1994
DOI: 10.1002/app.1994.070510106
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization characteristics of polypropylene and low ethylene content polypropylene copolymer with and without nucleating agents

Abstract: SYNOPSISIn this paper, the crystallization characteristics of polypropylene and low ethylene content polypropylene copolymers with and without nucleating agents were studied by differential scanning calorimetry (DSC) and polarized light microscopy ( PLM) . In order to determine the nonisothermal crystallization rate of these materials, a new estimation method was introduced. Comparing with the crystallization rate coefficient (CRC) , which was proposed by Khanna, we found the new approach is more reasonable. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 17 publications
1
46
0
Order By: Relevance
“…The values of b are larger than 1, which mean that the Avrami exponent n is always slight greater than the Ozawa exponent, m, as it has also been reported in literature. 36,37 Nucleation Activity…”
Section: Mo's Analysismentioning
confidence: 99%
“…The values of b are larger than 1, which mean that the Avrami exponent n is always slight greater than the Ozawa exponent, m, as it has also been reported in literature. 36,37 Nucleation Activity…”
Section: Mo's Analysismentioning
confidence: 99%
“…These observations are in good agreement with the characteristics of this compound, which has 16% of EPR phase 19 , dispersed in a polypropylene homopolymer matrix. The presence of the nucleating agent in one of the copolymers, PPcn, reduces the average spherulite size 20 , which tend to increases its impact strength in comparison with the unnucleated PPc 6 . Upon reducing the temperature the impact strength of the blends drops and the addition of up to 25% of elastomer has very little effect on the data.…”
Section: Izod Impact Strengthmentioning
confidence: 99%
“…The respective influence of nucleating agents (α or β) on the mechanical performances of heterophasic systems composed of an iPP matrix and an ethylene-propylene rubber (EPR) is still controversial, consequence of a lack of published experimental data. Whereas several studies have reported positive effects of nucleation on the fracture resistance of iPP/EPR blends [6][7][8][9][10][11][12], other contributions showed limited (for β-nucleation) [4,[13][14][15][16] or even negative (for α-nucleating agents) ones [4,17,18]. The goal of the present investigation was to identify potential coupling effect between the matrix crystalline structure induced by nucleation and the morphology of the rubbery phase in order to clarify this apparent contradiction.…”
Section: Introductionmentioning
confidence: 99%